Fish Bone Waste As Potential Source Of Apatite For Bone Replacement - Ivon, Tiew (Universiti Sains Malaysia, 2018)
In this research, multiphasic hydroxyapatite/β-tricalcium phosphate/carbonate apatite (HA/β-TCP/CO3Ap) scaffolds incorporated alginate was obtained. HA/β-TCP was obtained from Tilapia (Oreochromis mossambicus) fish bone by thermal calcination method. Slurry made of fish bone powder was used in freeze drying method to produce porous scaffold. The porous scaffold produced was then sintered up to 1200°C, 1300°C and 1400°C for 6 hours to convert HA into β-TCP or α-TCP phase. XRD analysis revealed that partial of the HA has transformed into β-TCP at sintering temperature 1200°C and 1300°C whereas HA, β-TCP and α-TCP were present at1400°C. Mechanical strength and density of porous scaffold increase with sintering temperature to 1300°C and decrease at 1400°C, whereas porosity is vice versa. HA/β-TCP/α-TCP scaffold obtained from 1400°C was chosen to transform into multiphasic HA/β-TCP/CO3Ap scaffold by dissolution-precipitation reaction with 2M of sodium carbonate (Na2CO3) at 200°C for 24 hours. Fourier transform infrared spectroscopy (FTIR) analysis confirmed the presence of characteristic functional groups of carbonate after dissolution-precipitation reaction. Multiphasic HA/β-TCP/CO3Ap scaffold was then coated with 5 wt% of sodium alginate solution. FTIR and scanning electron microscope (SEM) analysis confirmed the presence of sodium alginate after the coating was done on the multiphasic HA/β-TCP/CO3Ap scaffold. Mechanical strength of alginate coated multiphasic HA/β-TCP/CO3Ap scaffold was also increased compared to that of without coating.